Endoscopic diagnosis of megaesophagus in a buffalo - Vijayakumar, Govindarajan; Jegaveera-Pandian, Sankariah; Venkatesakumar, Elumalai; Kathirvel, Shanmugam; Subramanian, Mayilvahanam; Dharmaceelan, Saravanamuthu (Buffalo Bulletin, 2016)
A graded Murrah, she-buffalo (Bubalus bubalis) was presented with clinical signs of anorexia, occasional cough and regurgitation through nostrils and mouth for the past 15 days. Physical examination revealed fluctuation on the ventral neck and rumen intubation caused discomfort and regurgitation of watery, greenish ingesta through nostrils and mouth. Plain and contrast radiography of the neck was carried out. Endoscopy was performed as per standard procedure to visualize the esophagus and bronchi. The animal was found to have severe esophageal dilatation with stagnated ingesta and mild aspiration into the trachea. Further, the esophageal dilatation was confirmed in contrast radiography of esophagus.